1987
DOI: 10.1016/0035-9203(87)90262-8
|View full text |Cite
|
Sign up to set email alerts
|

Density-dependent timing of defaecation by Rhodnius prolixus, and its implications for the transmission of Trypanosoma cruzi

Abstract: Transmission of Trypanosoma cruzi is crucially dependent on the timing of defaecation by their insect vectors. Experimental studies on Rhodnius prolixus nymphs revealed a negative correlation between blood meal weight and defaecation time. Bugs which fed to repletion defaecated on average 7 min after feeding, whereas bugs with interrupted feeds defaecated about 1 h later. As blood meal weight of triatomine bugs is density-dependent, these results suggest that the greatest risk of successful T. cruzi transmissi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
10
0

Year Published

1990
1990
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(11 citation statements)
references
References 1 publication
1
10
0
Order By: Relevance
“…The dependence of defaecation time on the quantity of blood ingested was also observed for T. infestans (Trumper & Gorla 1991) and R. prolixus (Kirk & Schofield 1987). The relationtively did not defaecate.…”
Section: Discussionmentioning
confidence: 59%
“…The dependence of defaecation time on the quantity of blood ingested was also observed for T. infestans (Trumper & Gorla 1991) and R. prolixus (Kirk & Schofield 1987). The relationtively did not defaecate.…”
Section: Discussionmentioning
confidence: 59%
“…The dependence of defecation time on the quantity of ingested blood was observed in T. infestans (Trumper & Gorla 1991) and Rhodnius prolixus (Kirk & Schofield 1987); these two variables show a similarity in the feedingdefecation interval. A minimum blood feeding of 80 mg was enough for defecations to occur during feeding by 5 th instar nymphs, while nymphs of the 5 th instar of T. infestans, which fed on the same quantity of blood, had a feeding-defecation interval of 15 min after feeding (Trumper & Gorla 1991).…”
Section: Discussionmentioning
confidence: 88%
“…These data may predict differences between the abilities of these species as vectors (Mello 1980, Kirk & Schofield 1987, Trumper & Gorla 1991, Crocco & Catalá 1996.…”
mentioning
confidence: 99%
“…This strengthens the view that the threshold domestic abundance of T. infestans below which transmission of T. cruzi to dogs and cats is unlikely was very low, if any threshold exists at all, and undetectable within the imprecision of vector sampling methods. Experimental studies showed that bloodmeal size of triatomine bugs correlated negatively with time to first defecation which, combined with other laboratory and field studies, was used to suggest that low-density bug populations with increased feeding success would pose the greatest risk of T. cruzi transmission (Kirk and Schofield, 1987). While the likelihood of transmission per feeding contact with the host may or may not increase at low bug densities, the cumulative probability of T. cruzi transmission over all feeding contacts between bugs and hosts during the relevant exposure period will increase with increasing densities of infected bugs (Fig.…”
Section: Discussionmentioning
confidence: 95%